Plant-derived compounds for treating autosomal dominant polycystic kidney disease - Zhang, Jieting; Chen, Jiaxin; Xu, Jing; Xue, Cheng; Mao, Zhiguo (Frontiers in Nephrology, 2023)
Autosomal dominant polycystic kidney disease (ADPKD), the most common monogenic hereditary kidney disease, is the fourth leading cause of end-stage kidney disease worldwide. In recent years, significant progress has been made in delaying ADPKD progression with different kinds of chemical drugs such as tolvaptan, rapamycin, and somatostatin. Meanwhile, numerous plant-derived compounds also have been explored for their beneficial effects on slowing ADPKD progression. Among them, Saikosaponin-d, Ganoderma triterpenes, curcumin, Ginkgolide B, steviol, resveratrol, Sparganum stoloniferum Buch.-Ham, Cordyceps sinensis, Triptolide¬¬, quercitrin, naringin, cardamonin, gambogic acid, and olive leaf extract have been found to retard renal cyst development by inhibiting the proliferation or promoting cell apoptosis in renal cyst-lining epithelial cells. Metformin, a synthesized compound derived from the French lilac or goat's rue (Galega officinalis), has been proven to retard the progression of chronic kidney disease in ADPKD. This review focused on the efficacy, safety, and mechanism of these plant-derived compounds in treating ADPKD and may constitute promising new therapeutics in the future.